Methyl thiophanate-induced toxicity in liver and kidney of adult rats: a biochemical, molecular and histopathological approach - Feki, A.; Ben Saad, H.; Jaballi, I.; Magne, C.; Boudawara, O.; Zeghal, K. M.; Hakim, A.; Ben Ali, Y.; Ben Amara, I. (Cellular and Molecular Biology, 2017)
The aim of this study was to elucidate the redox effects of Thiophanate methyl (MT) in the rat liver and kidney. Our results showed, after 3 days of MT injection (700 mg/kg), an increase in malondialdehyde (MDA), hydrogen peroxide and advanced oxidation protein products levels. Glutathione peroxidase and superoxide dismutase activities were also remarkably increased in the liver but decrease in the kidney. Glutathione and vitamin C values were significantly reduced. The changes in biochemical parameters were substantiated by histological and molecular data. A smear without ladder formation on agarose gel was shown, indicating random DNA degradation in the liver and the kidney of MT treated rats. The increase in cyclooxygenase-2 gene expression, marker of inflammation, and an increase in genes expression of glutathione peroxidase and superoxide dismutase in liver and their decrease in the kidney were also occurred after MT exposure. These data confirmed the pro-oxidant and genotoxic effects of this fungicide.